NATIONAL MANIFESTATIONS IN THE WORK OF PROFESSIONAL KAZAKH ARTISTS (1980-2000) - B.R. Kаrаbаlаеvа, (Academic Journal of Physical and Chemical Sciences, 2019)
One of the main ideas of the worldview is a magnificent painting of a painting of a country in the world of Kazakh painting. Therefore, it is necessary to clarify the paths and continuity of the ancient Russian art of Kazakhstan in modern art, based on the laws of the sphere of art. This is because it allows you to analyze regular forms and essence, images and symbols of works of art that are traditionally practiced at the present time.The article identifies significant changes in the Kazakh pictorial art from 1980 to 2000. The traditions of national traditions, the mythical and Turkic worldview are reflected in the works of Kazakh artists. Kazakh artists came from schools of European and Russian art and studied the roots of the Turkic peoples during the years of independence. Describing the history of their ancestors, the artists made every effort to create national clothing and ethnographic values, as well as the foundations of worldview. It is clear that the work of these artists are philosophical and mythological in nature. Drawing on traditional images in their works, artists promote worldview, mythology, and philosophy in its understanding.